Bayesian estimation of extropy and goodness of fit tests. Issue 2 (25th January 2022) - Al-Labadi, Luai; Berry, Sean
Abstract : Extropy, a complementary dual of entropy, is considered in this paper. A Bayesian approach based on the Dirichlet process is proposed for the estimation of extropy. A goodness of fit test is also developed. Many theoretical properties of the procedure are derived. Several examples are discussed to illustrate the approach.